2019
DOI: 10.3390/cancers11020227
|View full text |Cite
|
Sign up to set email alerts
|

Infiltration of FoxP3+ Regulatory T Cells is a Strong and Independent Prognostic Factor in Head and Neck Squamous Cell Carcinoma

Abstract: Head and Neck Squamous Cell Carcinomas (HNSCC) are characterized by a large heterogeneity in terms of the location and risk factors. For a few years now, immunotherapy seems to be a promising approach in the treatment of these cancers, but a better understanding of the immune context could allow to offer a personalized treatment and thus probably increase the survival of HNSCC patients. In this context, we evaluated the infiltration of FoxP3+ Tregs on 205 human formalin-fixed paraffin-embedded HNSCC and we ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 39 publications
5
70
0
1
Order By: Relevance
“…The microenvironment of immunodepression is characterized by the infiltration of immune cells such as Tregs [9]. Strong infiltration of forkhead/winged-helix transcription factor box P3 (FoxP3) + Tregs in HNSCC is associated with improved OS [33,34]. Likewise, our results also demonstrate that Tregs were enriched in low immune risk groups.…”
Section: Discussionsupporting
confidence: 57%
“…The microenvironment of immunodepression is characterized by the infiltration of immune cells such as Tregs [9]. Strong infiltration of forkhead/winged-helix transcription factor box P3 (FoxP3) + Tregs in HNSCC is associated with improved OS [33,34]. Likewise, our results also demonstrate that Tregs were enriched in low immune risk groups.…”
Section: Discussionsupporting
confidence: 57%
“…In cancer, Tregs contribute to tumor immune escape by suppressing the antitumor response. Some studies had reported that higher Foxp3 + Treg cell infiltration was associated with poorer patient survival in most tumors, but not in HNSCC [48,49]. Our results show that the high level of Tregs infiltration is significantly associated with the low risk score, which is associated with favorable prognosis.…”
Section: Genetic Alterations and Gsea Analysis In The High-risk Groupssupporting
confidence: 42%
“…This disruption induced tumor‐promoting Treg differentiation, and increased anti‐inflammatory cytokine Interleukin 10 (IL‐10) production in HNSCCs 47,48 . On the other hand, a high level of FoxP3 + Treg infiltration in HNSCCs was associated with longer RFS and OS 22,49 . This is probably because the presence of a high level of FoxP3 + Treg in tumors indicates an on‐going robust antitumor immune response, which contributes to inhibition of tumor growth.…”
Section: T Cellsmentioning
confidence: 99%